The relationship of service quality dimensions of restaurant enterprises with satisfaction, behavioral intention, eWOM and the moderator effect of atmosphere - Abdullah Uslu (Tourism & Management Studies)
This research is carried out in order to test the relationship between the service quality of restaurants, electronic word-of-mouth communication (eWOM), satisfaction and behavioral intention, and to analyze the moderator effect of the restaurant atmosphere in the relationship between service quality and eWOM. The population of the research is the local tourists who come to the restaurants located in the city center of Diyarbak?r. Questionnaires have been used to obtain the data of the research. The data has been analyzed using 385 surveys collected from restaurant customers using package programs (SPSS and AMOS). As a result of the analysis, service quality dimensions have been determined as 4 dimensions (tangibles, assurance, reliability and empathy) in restaurants. Then CFA (confirmatory factor analysis) and second order CFA, measurement model and path analyses have been carried out. According to the results of the analysis, it has been determined that the service quality dimensions of the restaurants have effects on satisfaction and eWOM. In addition, restaurant atmosphere has been found to have a moderator effect on the effect of service quality dimensions on eWOM in restaurants